1980
DOI: 10.1111/j.1600-0773.1980.tb02468.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Xylene and Alcohol on the Central Nervous System

Abstract: Absrracr: Ten healthy male students were exposed to m-xylene alone at concentrations of about 6 and 11.5 pmol/l and given a single dose of alcohol (0.4 and 0.8 g/kg) prior to exposure. The effects of these xylene concentrations and alcohol doses, as well as the combined effects of the two xylene concentrations with the higher alcohol dose on psychophysiological functions, such as body balance and reaction time, were assessed. Xylene alone did not significantly impair these functions, although there was a tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 13 publications
0
2
1
1
Order By: Relevance
“…The present results showed that alcohol caused no changes in the eyes closedlopen ratio, but it dose-dependently increased body sway (Savolainen 1980), a finding which suggests an unspecific depressant action of alcohol on the CNS. Theslight response by the larger alcohol dose alone was delayed although of similar size than that of the smaller one.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The present results showed that alcohol caused no changes in the eyes closedlopen ratio, but it dose-dependently increased body sway (Savolainen 1980), a finding which suggests an unspecific depressant action of alcohol on the CNS. Theslight response by the larger alcohol dose alone was delayed although of similar size than that of the smaller one.…”
Section: Discussioncontrasting
confidence: 46%
“…A decrease in the ratio during increased body sway might then indicate involvement of central visual pathways (relative increase of body sway with the eyes open) or tolerance (decreased body sway with the eyes closed), while an increased ratio might suggest an effect directed towards the equilibrium system (Savolainen & Riihimaki 1981). The relatively more pronounced changes take place when the eyes are closed, at least when xylene is concerned (Savolainen et al 1979;Savolainen 1980;Savolainen et al 1980a & b). In the present type of study disturbances in equilibrium are probably not due to disturbances of the peripheral proprioreceptive system, since considerably longer exposure to chemical agents is needed to induce dysfunctions of the peripheral nervous system (Schaumburg & Spencer 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Motor speed is one aspect of performance that may be slowed by exposure to neurotoxicants such as alcohol ( Savolainen 1980 ). On this test of motor speed ( Letz 1998 ), the subject was instructed to tap a keyboard button as many times as possible within a 30-sec interval.…”
Section: Methodsmentioning
confidence: 99%
“…Eine vierstündige Exposition mit 640 mg/m 3 oder 1200 mg/m 3 hatte bei 10 Probanden keinen Einfluss auf Gleichgewichtssinn und Flimmerverschmelzungsfrequenz [52]. Dagegen wurden Gleichgewichtssinn und Sehfähigkeit durch 4 h Exposition gegenüber 880 mg m-Xylol/m 3 beeinträch-tigt [53,54], bei 640 mg m-Xylol/m 3 waren die Effekte auf den Gleichgewichtssinn nicht konsistent und die Sehfähig-keit nicht beeinflusst [52,55].…”
Section: Irritative Wirkungenunclassified